PARTICIPATORY CULTURE OF COLLEGE STUDENTS OF SALEM IN SOCIAL MEDIA - T, Sundara Raj. (International Journal of Psychosocial Rehabilitation, 2020)
Computer assisted technologies help in the creation and dissemination of information, thoughts, career interests and other forms of manifestations through virtual communities and networks are commonly referred as social media. Studies show that social media usage especially, among the youth, is increasing at an alarming rate. People use social media differently for a range of purposes. Several are active users of social media as some are participatory users. This paper utilised primary data to find out the participatory culture in social media among the college students in Salem district, Tamil Nadu. The study was conducted among the Arts and Science college students in Salem city. 200 students in the age group of 18 to 21 years were randomly selected as a sample. The findings of the study show that 81 percent of the respondents are ‘active users’ of social media and 19% are ‘participatory users’ who are involved in the process of content creation through media. The content creators are also found to be involved in social activities in their respective communities.